Angelika Molnar: Text, Genre, Word: Studies in Russian literature of the 19th–21st centuries. Moscow, Azbukovnik 2022, 424 pp. ISBN 978-5-91172-221-0 - Belyaeva, Irina (Slavica, 2022)
This review contains a critical analysis of Angelika Molnar’s new book, her monograph entitled Text, genre, word: Studies in the Russian literature of the 19th-21st centuries is devoted to various texts of different eras from Pushkin’s to Sorokin’s, however, the focus of the study is Molnár’s favorite Russian writer, Goncharov, whose work, unfortunately, rarely attracts the attention of Western researchers. In Molnár’s book, the main, clearly indicated methodological principle is discursive poetics, which works well when studying intertexts within the framework of both large and small literary and historical series. Therefore, Russian literature is considered by the researcher as a single text in which the "old" is updated by the "new". The review emphasizes the significance of the monograph, which first of all offers an up-to-date interpretationof Russian classics in the context of modernity. The book will be of interest both to a professional researcher of Russian literature and to everyone who is interested in Russian culture and the Russian worldview.